2021
DOI: 10.15420/cfr.2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Heart Block After Transcatheter Aortic Valve Replacement

Abstract: Transcatheter aortic valve replacement (TAVR) has developed substantially since its inception. Improvements in valve design, valve deployment technologies, preprocedural imaging and increased operator experience have led to a gradual decline in length of hospitalisation after TAVR. Despite these advances, the need for permanent pacemaker implantation for post-TAVR high-degree atrioventricular block (HAVB) has persisted and has well-established risk factors which can be used to identify patients who are at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Baseline right bundle branch block (RBBB) is a major electrical disturbance, independent of age or left ventricular ejection fraction, 9 increasing the risk for atrioventricular block (AVB) leading to PPI 4–8,10–16 . In contrast, preexisting LBBB was previously known not to increase the risk of post‐TAVR conduction abnormalities 8,9,15,17,18 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Baseline right bundle branch block (RBBB) is a major electrical disturbance, independent of age or left ventricular ejection fraction, 9 increasing the risk for atrioventricular block (AVB) leading to PPI 4–8,10–16 . In contrast, preexisting LBBB was previously known not to increase the risk of post‐TAVR conduction abnormalities 8,9,15,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…However, based on five observational cohort studies recruiting a total of 1901 patients, Ullah et al 15 found that age >80 was not a statistically significant predictor of PPI, and the risk is comparable to younger patients (OR: 1.19; 95% CI: 0.95–1.49). Furthermore, male sex is a risk factor for periprocedural PPI, independent of age, ventricular function, type of prosthesis, or access site 4,5,12,15,26 . A possible explanation may be that male patients receive larger THVs and have more preprocedural comorbidities compared to female patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations